DEVELOPMENT OF LETTUCE FERTILIZED WITH BOVINE BIOFERTILIZER AND IRRIGATED WITH TWO WATER LAYERS - Chiconato, Denise Aparecida; Galbiatti, João Antonio; Maldonado Junior, Walter; Franco, Claudenir Facincani; Caramelo, Anaira Denise (Comunicata Scientiae, 2014)
In order to evaluate the effects of cattle biofertilizer and irrigation in lettuce (Lactuca sativa L.) for a possible replacement for organic fertilizers, and also decrease water for irrigation, this research was developed, using an experimental design in randomized blocks, factorial scheme 6x2, with six levels of fertilization (4 doses of bovine biofertilizer and two witnesses: without fertilizer and mineral fertilizer) and two irrigation layers (80 and 100% of reference evapotranspiration) with four replications, in the field . The variables analyzed were: height, head diameter, chlorophyll, leaf number, fresh weight and dry weight of plant tops. It was performed by analysis of variance of F test, comparison of means by Tukey test (p <0.05) and polynomial regression. The results showed that the levels of biofertilizer were similar to the mineral control, pointing the possibility to replace them with the dose of 90m3ha-1 more recommendable, and the best water layer, of 80% of the evaporation.